Hindlimb unloading producing effects on bone biomechanical properties in mature male rats - Carvalho, A. A F [UNESP] (2007)
Aging is associated with decline in muscle mass and strength and reduced bone density. Age-related bone loss is a primary factor in osteoporosis and all individuals are potential candidates for osteoporosis because bone loss with aging occurs in men and women, but less studied in men. To examine the appropriateness of hindlimb elevation, by tail suspension as a model for diminished mechanical loading, and to determine the influence of age on bone responsiveness to skeletal unloading, we use dual X ray absorptiometry (DXA) and digital radiographic images to analyze the response of the femur from mature rats to biomechanical loads. Femurs from male Wistar rats (9-mo-old) were scanned using DXA and DIGORA and measures obtained in ephipyseal and diaphyseal regions of interest. The mechanical testing was divided into compression load to fracture the head and a three-point bending load to fracture the femur middiaphysis. In femoral epiphysis from hindlimb unload (HU), animals presented significant differences between mineral bone content and density assessed by DXA. Detailed regions of femoral epiphysis (head, throcanteric fossa, throcanter and metaphysis) presented significant lower values from radiographic density. Only compressive load necessary to fracture the femoral head neck was also significantly diminished in HU animals. Disuse induced, as in elderly patients, deterioration of the trabecular bone architecture with critical effect on bone fragility. Rats with 21 days of hindlimb unloading can simulate disuse, suggesting that certain sub-regions of their aging bones are more susceptible to fracture, while other, i.e. diaphyses, are not.